The β1 Subunit Enhances Oxidative Regulation of Large-Conductance Calcium-activated K(+) Channels - Santarelli, Lindsey Ciali (The Rockefeller University Press, 2004)
Oxidative stress may alter the functions of many proteins including the Slo1 large conductance calcium-activated potassium channel (BK(Ca)). Previous results demonstrated that in the virtual absence of Ca(2+), the oxidant chloramine-T (Ch-T), without the involvement of cysteine oxidation, increases the open probability and slows the deactivation of BK(Ca) channels formed by human Slo1 (hSlo1) α subunits alone. Because native BK(Ca) channel complexes may include the auxiliary subunit β1, we investigated whether β1 influences the oxidative regulation of hSlo1. Oxidation by Ch-T with β1 present shifted the half-activation voltage much further in the hyperpolarizing direction (−75 mV) as compared with that with α alone (−30 mV). This shift was eliminated in the presence of high [Ca(2+)](i), but the increase in open probability in the virtual absence of Ca(2+) remained significant at physiologically relevant voltages. Furthermore, the slowing of channel deactivation after oxidation was even more dramatic in the presence of β1. Oxidation of cysteine and methionine residues within β1 was not involved in these potentiated effects because expression of mutant β1 subunits lacking cysteine or methionine residues produced results similar to those with wild-type β1. Unlike the results with α alone, oxidation by Ch-T caused a significant acceleration of channel activation only when β1 was present. The β1 M177 mutation disrupted normal channel activation and prevented the Ch-T–induced acceleration of activation. Overall, the functional effects of oxidation of the hSlo1 pore-forming α subunit are greatly amplified by the presence of β1, which leads to the additional increase in channel open probability and the slowing of deactivation. Furthermore, M177 within β1 is a critical structural determinant of channel activation and oxidative sensitivity. Together, the oxidized BK(Ca) channel complex with β1 has a considerable chance of being open within the physiological voltage range even at low [Ca(2+)](i).